Development of the observation of membrane fusion with label-free liposomes by calcium imaging - Morihiro Hotta; Kengo Hayase; Aya Kitanaka; Tianshu Li; Shinji Takeoka (Biochemistry and Biophysics Reports, 2023)
Liposomes are artificial vesicles composed of lipid bilayers that have enabled drugs to be encapsulated and delivered to tumor tissue. Membrane-fusogenic liposomes fuse with the plasma membranes of cells to deliver encapsulated drugs directly to the cytosol, which makes it a promising method for rapid and highly efficient drug delivery. In a previous study, liposomal lipid bilayers were labeled with fluorescent probes, and colocalization of labeled lipids with plasma membrane was observed under a microscope. However, there was concern that fluorescent labeling would affect lipid dynamics and cause liposomes to acquire membrane fusogenic ability. In addition, encapsulation of hydrophilic fluorescent substances in the inner aqueous phase sometimes requires an additional step of removing unencapsulated substances after preparation, and there is a risk of leakage. Herein, we propose a new method to observe cell interaction with liposomes without labeling. Our laboratory has developed two types of liposomes with different cellular internalization pathways, i.e., endocytosis and membrane fusion. We found that cytosolic calcium influx would be triggered following the internalization of cationic liposomes, and different cell entry routes led to different calcium responses. Thus, the correlation between cell entry routes and calcium responses could be utilized to study liposome-cell interactions without fluorescent labeling lipids. Briefly, liposomes were added to phorbol 12-myristate 13-acetate (PMA)-primed THP-1 cells, and calcium influx was measured by time-lapse imaging using a fluorescent indicator (Fura 2-AM). Liposomes with high membrane fusogenic ability elicited a strong transient calcium response immediately after adding liposomes, whereas those taken up mainly by endocytosis elicited multiple weak calcium responses. In order to verify the cell entry routes, we also tracked the intracellular distribution of fluorescent-labeled liposomes in PMA-primed THP-1 cells using a confocal laser scanning microscope. It was shown that for fusogenic liposomes, colocalization with plasma membrane occurred at the same time as calcium elevation, whereas for liposomes with a high endocytosis potential, fluorescent dots were observed in the cytoplasm, suggesting the cell internalization by endocytosis. These results suggested that the calcium response patterns correspond to cell entry routes, and membrane fusion can be observed by calcium imaging.